THE EFFECT OF STUDENT’S PERCEPTION ON THE SCHOOL ENVIRONMENT AND LEARNING INTEREST TOWARD ENGLISH LEARNING ACHIEVEMENT - Alfian, Alfian; ULhaq, Munsyi (Eduscience : Jurnal Ilmu Pendidikan, 2020)
AbstractThis present study is aimed at seeking out whether or not there is a significant contribution regarding student’s perception on the school environment and learning interest toward English leearning achievement. It is a survey research with correlational analysis used as its basic design for both analyzing the data and testing hypothesis. The collected data were analyzed using statistical regression and correlation techniques. Based on the results of data analysis and hypothesis testing, it shows that There is a significant influence jointly on Perception on School Environment and Learning Interests on the Learning Achievement of English students of Mahadhika 4 Vocational High School Jakarta. It was proven by an F count of 82.799 and sig = 0.000 <0.05. There is a significant influence of Perception on School Environment on the English Language Learning Achievement of Mahadhika 4 Jakarta Vocational High School students. It is proven by the t value of 3.374 and sig = 0.000 <0.05. There is a significant influence of Learning Interest on English Learning Achievement of Mahadhika 4 Jakarta Vocational High School students. It is proven by the t value of 10.818 and sig = 0.000 <0.05. Key words: school environment, learning interest, learning achievement AbstrakPenelitian ini bertujuan untuk mengetahui ada atau tidaknya kontribusi yang signifikan mengenai persepsi siswa tentang lingkungan sekolah dan minat belajar terhadap prestasi belajar bahasa Inggris. Ini adalah penelitian survei dengan analisis korelasional yang digunakan sebagai desain dasar untuk menganalisis data dan menguji hipotesis. Data yang dikumpulkan dianalisis menggunakan regresi statistik dan teknik korelasi. Berdasarkan hasil analisis data dan pengujian hipotesis, diketahui bahwa ada pengaruh yang signifikan secara bersama-sama persepsi siswa terhadap lingkungan Sekolah dan Minat Belajar terhadap Prestasi Belajar Bahasa Inggris Siswa Sekolah Menengah Mahadhika 4 SMK Jakarta. Itu dibuktikan dengan F hitung 82,799 dan sig = 0,000 <0,05. Ada pengaruh yang signifikan dari Persepsi terhadap Lingkungan Sekolah terhadap Prestasi Belajar Bahasa Inggris siswa SMA Mahadhika 4 Jakarta. Hal ini dibuktikan dengan nilai t sebesar 3,374 dan sig = 0,000 <0,05. Ada pengaruh yang signifikan Minat Belajar terhadap Prestasi Belajar Bahasa Inggris siswa SMA Mahadhika 4 Jakarta. Hal ini dibuktikan dengan nilai t sebesar 10,818 dan sig = 0,000 <0,05Kata kunci: lingkungan sekolah, minat belajar, prestasi belajar